Strategic Framework for Achieving Sustainability in Telecom Supply Chain, a Case Study of Pakistan - Syed Hassan Raza; Asher Ramish; Khaliq-Ur-Rehman (Market Forces, 2022)
Current research aims to unpack the issues faced by the telecom sector of Pakistan to sustain its supply chain management. While using the qualitative case study method, this research has analyzed the available framework to achieve sustainability in the supply chain. The study used data triangulation and extracted data from Telecom company’s documentation, on-site observation & semi-structured interviews. Based on primary and secondary data, we have proposed a strategic framework for developing sustainability in the supply chain of telecom companies. The framework provides the step-by-step implementation of all dimensions of sustainability upstream of a supply chain. The developed framework can be used as a roadmap by the Telecom sector to make their supply chain more sustainable. The research focuses on the upstream supply chain, and the findings argue that telecom supply chains can only use the proposed framework upstream to achieve sustainability.